Composition and abundance of the Stomach Contents of Caranx melampygus in Nabinbinan Bay, Nueva Valencia, Guimaras - Caigoy, Mary Johnalynn S.
Caranx melampygus, a piscivore common in the Indo-Pacific, is an important diurnal predator in coral reefs but little local information is available on the diet of this fish. This study was done to determine the diet composition and abundance of C. melampygus by examining the stomach contents of specimens collected every 2-4 weeks from catches of fish corals in Southern Guimaras from May 2012 to November 2013. Chyme, fishes, and shrimps were found in the guts of C. melampygus. The Sergestid shrimp Acetes dominated the overall prey composition, followed by penaeid shrimps, and fishes (atherinid, clupeid, engraulid). The mean food count and prey composition varied among small (6-6.9, 7-7.9, 8-8.9), medium (9-9.9, 10-10.9, 11-11.9), and large (12-12.9, 13-13.9, 14-14.9, 15-15.9) fish, suggesting that the food preference of C. melampygus changes as the fish grows.